Proceedings 2014 Network and Distributed System Security Symposium 2014
DOI: 10.14722/ndss.2014.23097
|View full text |Cite
|
Sign up to set email alerts
|

Inside Job: Understanding and Mitigating the Threat of External Device Mis-Bonding on Android

Abstract: Abstract-Today's smartphones can be armed with many types of external devices, such as medical devices and credit card readers, that enrich their functionality and enable them to be used in application domains such as healthcare and retail. This new development comes with new security and privacy challenges. Existing phone-based operating systems, Android in particular, are not ready for protecting authorized use of these external devices: indeed, any app on an Android phone that acquires permission to utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 18 publications
3
78
0
Order By: Relevance
“…We found that under the strategy for selecting suspicious processes, only 1.68% of the popular apps with perceptible impacts on user experience needed to be closed when they were running in the background and all of them could be swiftly restored without losing their runtime states. Our study further shows that the new technique defeated all known RIG attacks, including audio recording, Bluetooth misbonding [6], a series of side-channel attacks on high-profile apps [1], [4], [5], [20], the recently proposed user-interface inference [2] and voice eavesdropping [7], together with the new IoT attacks we discovered, at a performance cost as low as 5% of CPU time and 40 MB memory.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…We found that under the strategy for selecting suspicious processes, only 1.68% of the popular apps with perceptible impacts on user experience needed to be closed when they were running in the background and all of them could be swiftly restored without losing their runtime states. Our study further shows that the new technique defeated all known RIG attacks, including audio recording, Bluetooth misbonding [6], a series of side-channel attacks on high-profile apps [1], [4], [5], [20], the recently proposed user-interface inference [2] and voice eavesdropping [7], together with the new IoT attacks we discovered, at a performance cost as low as 5% of CPU time and 40 MB memory.…”
Section: Introductionmentioning
confidence: 56%
“…More recently, research has found that Android Bluetooth accessories are also vulnerable to such runtime data stealing [6]. The official app of a Bluetooth medical device, such as blood-glucose meter and pulse oximeter, can be monitored by a malicious app with the Bluetooth permission.…”
Section: A Background and Prior Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3]. Also, a Bluetooth operated medical device's genuine app can give away a vital information [6]. A big concern here is that even zero permission can still gain highly profound data from a variety of side channels, signifying the important weakness of mobile devices in extrication an app's operations from its data.…”
Section: Introductionmentioning
confidence: 99%
“…As the value of incentives increase, users could be more tempted to cheat when reporting their per-formance [20], which would endanger the viability of the system for the service provider and its affiliates, as well as its attractiveness to the users. For example, location cheating can be achieved by making mobile devices report erroneous location information to the activity-tracking app [21], [22], or by spoofing the GPS/Wi-Fi signals used for geo-location users [23]- [25]. Moreover, some tools enable users to manipulate activity data to lie about their performance [26]- [28].…”
Section: Introductionmentioning
confidence: 99%